2018
DOI: 10.1166/jnn.2018.15261
|View full text |Cite
|
Sign up to set email alerts
|

TiO2/Ag–TiO2 Nanohybrid Films are Cytocompatible with Primary Epithelial Cells of Human Origin: An In Vitro Study

Abstract: Failure of dental implants is caused mainly by peri-implant infections resulting in loss of supporting bone. Since there is no ideal therapy of peri-implantitis, the focus of research has been shifted toward better prevention and the development of antibacterial surfaces. In our study we examined the attachment and proliferation of primary epithelial and MG-63 osteosarcoma cells on Ti dental implants coated with photocatalytic nanohybrid films. Two polyacrylate resin based layers were investigated on commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The study design varied in terms of TiO 2 coating techniques. Five of the selected studies used sol-gel derived TiO 2 coatings [ 31 , 33 , 35 , 38 , 41 ]; three used HT-induced TiO 2 coating [ 32 , 34 , 37 ]; one used the vapor deposition method [ 39 ]; one used spray coating technique [ 36 ]; and one used peroxotitanium acid solution as a chemical coating method [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study design varied in terms of TiO 2 coating techniques. Five of the selected studies used sol-gel derived TiO 2 coatings [ 31 , 33 , 35 , 38 , 41 ]; three used HT-induced TiO 2 coating [ 32 , 34 , 37 ]; one used the vapor deposition method [ 39 ]; one used spray coating technique [ 36 ]; and one used peroxotitanium acid solution as a chemical coating method [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The sterilization method was described in eight studies, five of which used autoclaves [ 31 , 32 , 34 , 39 , 41 ]. The remaining three studies used UV light [ 36 , 37 , 40 ]. Regarding the biological evaluation, two studies were performed on the tissue culture models [ 32 , 33 ], whereas the other studies were conducted on human gingival fibroblasts (HGFs) [ 37 , 38 , 39 , 40 , 41 ] or epithelial cells [ 31 , 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Roland Masa et al found that Ag-TiO 2modified implant samples were not toxic to human epithelial cells and MG-63 osteosarcoma cells by MTT assay. 31 Cotolan et al demonstrated that the presence of silver in Nano-Ag-TiO 2 does not damage human osteoblastoma cells and has potential applications in the biomedical field. 32 Nano-Ag-TiO 2 not only solves the shortcomings of TiO 2 antibacterial agents that need to use light to function, 33,34 but also has higher bactericidal activity than pure silver (Ag) nanoparticles, 35 and also solves the problem that silver antibacterial agents are prone to discoloration.…”
Section: Introductionmentioning
confidence: 99%
“…Nano‐Ag‐TiO 2 can slow down the release of silver ions and reduce the cytotoxicity of silver while obtaining certain antibacterial properties. Roland Masa et al found that Ag‐TiO 2 ‐modified implant samples were not toxic to human epithelial cells and MG‐63 osteosarcoma cells by MTT assay 31 . Cotolan et al demonstrated that the presence of silver in Nano‐Ag‐TiO 2 does not damage human osteoblastoma cells and has potential applications in the biomedical field 32 .…”
Section: Introductionmentioning
confidence: 99%
“…4 Masa and his colleagues, 2018 reported that TiO 2 has a property to attach with human epithelial cells along with a good tolerability. 5 TiO 2 nanoparticles interact instantly with the buccal mucosa upon contact and show a long residence time in the oral cavity. 6 Aceclofenac is a widely used Biopharmaceutics Classification System (BCS) class II non-steroidal anti-inflammatory drug (NSAID).…”
Section: Introductionmentioning
confidence: 99%